2020
DOI: 10.31248/rjfsn2020.091
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of selected street vended foods during wet and dry season in parts of Port Harcourt metropolis, Rivers State, Nigeria

Abstract: Microbiological quality of selected ready-to-eat (RTE) street vended foods (SVF) were determined to evaluate the impact of wet and dry seasons on food safety in 3 locations (Makoba-station 1, Elekahia-station 2 and Rivers State University-station 3). Six food products investigated were roasted plantain (RP), roasted fish (RF), roasted yam (RY), suya (SY), meat pie (MP) and doughnuts (DN). Total Aerobic Count (TAC), Total Coliform Count (TCC), Faecal Coliform Count (FCC), Total Staphylococcus Count (TSC), Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results obtained were generally higher than acceptable limits, and those of S. aureus were also high. Oyet et al (2020) reported from Rivers State using selected street-vended foods as test samples and found a high total Staphylococcal count (TSC) (6.00 to 8.00 log10 CFU/g) in roasted fish in the rainy season.…”
Section: Contamination Of Food Of Animal Origin By S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained were generally higher than acceptable limits, and those of S. aureus were also high. Oyet et al (2020) reported from Rivers State using selected street-vended foods as test samples and found a high total Staphylococcal count (TSC) (6.00 to 8.00 log10 CFU/g) in roasted fish in the rainy season.…”
Section: Contamination Of Food Of Animal Origin By S Aureusmentioning
confidence: 99%
“…Proper storage and packaging (Ogofure and Igbinosa (2021) were also seen to reduce the occurrence of isolates in samples. Weather (rainy season) was also shown to have a resultant effect on the cultured isolates (Oyet et al 2020). Furthermore, safe handling of food alongside appropriate food processing practices, ensuring a cold chain, proper cleaning, and disinfecting equipment, limiting cross-contamination, and minimizing food contamination in all aspects of the food chain are necessary preventive measures (Kadariya et al 2014).…”
Section: Factors Influencing S Aureus Contamination Of Food Of Animal...mentioning
confidence: 99%
“…However, despite their economic, social and nutritional advantage, ready-to-eat street vended foods such as Awara and Moin-moin has been found to inflict potential foodborne hazard/disease [3][4][5][6] because the nature of their point of sell (the street) these foods are easily contaminated from different factors including the surrounding air, the water source and the food handlers [6]. Although street food vending is critical to food security in low-income countries [7] such as Nigeria, however there is no standard procedure for determining the risk of microbial, chemical and or toxicological hazard of the foods [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, from the handling perspective, Most of street food sellers are unhygienic, serving the foods with uncontrolled hand handling using bare hands making them becoming vehicle for microorganisms contamination through their hands, mouth, skin among others because they most at time did not practice proper personal hygiene or correct food preparation, [10,11]. Studies in Nigeria have linked street foods to frequent contamination with hazardous microorganisms, Oyet et al, [6] reported heavy contamination of street foods vended in Porthacourt streets with E. coli, Bacillus spp., Salmonella, S. aureous, and Mould. [5] reported contamination of meat pie, beef sausage roll, egg roll, peeled orange, walnut and apple on Onitsha-Warri with E. coli, Shigella spp.…”
Section: Introductionmentioning
confidence: 99%